Classifications of the Generalized Epilepsies - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:The classification of generalized epilepsy is characterized by conflicting tendencies on what purpose a classification should serve. It has evolved over the years to reflect these conflicting needs.Objective:We aim to review the various classifications of generalized epilepsy to evaluate their respective rationale, strengths, and weaknesses.Materials and Methods:A literature search of electronic databases supplemented by a search of cross-references was conducted. The search results were subjected to a narrative review.Results:Epilepsy classification is based primarily on the type of seizure, as well as evidence from clinical, neurological, electrophysiological, and neuroimaging evaluations. The main challenge of epilepsy classification is to balance the pragmatic needs of the clinician with the varied needs of the researcher. Various classifications of generalized epilepsy have been proposed but the most important are those proposed by the International League Against Epilepsy.Conclusions:We are a long way from an ideal classification that is grounded in evidence, flexible enough to accommodate new findings, and versatile enough to classify individual patients.